Electrochemical Activity of Nano-NiSi2 in Li Cells. Issue 10 (9th September 2016) - Du, Zhijia; Hatchard, T. D.; Bissonnette, P.; Dunlap, R. A.; Obrovac, M. N.
Abstract : Crystalline and nanocrystalline NiSi2 were studied as negative electrode materials in Li cells. Crystalline NiSi2 was found to be inactive toward lithiation/delithiation. However, it was found that NiSi2 becomes active toward lithium when made nanocrystalline by ball milling. X-ray diffraction peaks from nanocrystalline NiSi2 disappear after the first lithiation process, confirming its electrochemical activity. In subsequent cycles, the voltage curve of nanocrystalline NiSi2 is similar to that of amorphous Si, excepting that there is significant depression of the lithiation potential, which may arise from internal stress.